Penentuan Nilai Sun Protective Factor (SPF) Secara In Vitro Krim Tabir Surya Ekstrak Etanol Kulit Alpukat - Mokodompit, Ade Novia; Edy, Hosea Jaya; Wiyono, Weny (PHARMACON, 2013)
ABSTRACT Peel of avocado (Persea americana Mill) contain efficacious compounds as an antioxydant. This studyhave purpose to determinethe value of Sun Protective Factor (SPF) of sunscreen from avocado's peel extract (Persea americana Mill) with aconcentration of5%, 7.5% and 10%. In the determination of in vitro SPF valuesusing a spectrophotometer produce SPF values obtainedat a concentration of 5% is 3.99, 7.5% is 5.88,10% is 6.81. This study proves that the use of this creamis notefficaciousas a sunscreen because the value result of SPF not exceed the minimal limit of good sunscreen SPF, that is 15. Key word : Peel of avocado (Persea americana Mill), cream, value of Sun Protective Factor (SPF)